Eligibility of patients with type 2 diabetes for sodium–glucose cotransporter 2 inhibitor cardiovascular outcomes trials: a global perspective from the DISCOVER study. Issue 1 (21st March 2019) - Pintat, Stéphane; Fenici, Peter; Hammar, Niklas; Ji, Linong; Khunti, Kamlesh; Medina, Jesús; Tang, Fengming; Wittbrodt, Eric; Surmont, Filip
Abstract : Objective: To assess the eligibility of patients participating in DISCOVER (a 3-year, prospective, observational study program of 15 992 patients with type 2 diabetes [T2D] initiating a second-line glucose-lowering therapy across 38 countries) for four cardiovascular outcomes trials (CVOTs) of sodium–glucose cotransporter 2 inhibitors (CANagliflozin cardioVascular Assessment Study [CANVAS], Dapagliflozin effect on CardiovascuLAR Events trial [DECLARE-TIMI 58], EMPAgliflozin cardiovascular OUTCOME event trial [EMPA-REG OUTCOME], and eValuation of ERTugliflozin effIcacy and Safety CardioVascular outcomes trial [VERTIS-CV]). Research design and methods: In this cross-sectional analysis, baseline characteristics of DISCOVER patients were compared with the inclusion and exclusion criteria of the CVOTs to assess patient eligibility, overall and in four regions (Asia-Pacific, Europe, Latin America, and Middle East and Africa). Results: Overall, 11 385 patients (71.2%) had sufficient data for the analysis; 56.1% were men. The mean age and time since T2D diagnosis were 57.4 and 5.6 years, respectively. The mean glycated hemoglobin level was 8.3%. DISCOVER patients were younger, and fewer had a history of cardiovascular disease, than those enrolled in the CVOTs. Eligibility varied across the CVOTs; the proportion of eligible DISCOVER patients was highest for DECLARE-TIMI 58 (40.5%), followed by CANVAS (19.9%), VERTIS-CV (7.2%), and EMPA-REG OUTCOME (7.1%); 54.6% of patients were not eligible for any CVOT. Eligibility for each CVOT varied across regions, which was explained by the differing proportions of patients with established cardiovascular disease. Conclusions: In a large, international population of patients with T2D initiating a second-line glucose-lowering therapy, DECLARE-TIMI 58 was the most inclusive CVOT, suggesting that its study population will be more representative of patients encountered in routine clinical practice than those of CANVAS, EMPA-REG OUTCOME, and VERTIS-CV.